2002
DOI: 10.1086/338674
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Performance Measure Choices in Worker Incentive Plans

Abstract: This study examines the determinants of performance measure choices in worker incentive plans. The results indicate that inform-ativeness issues such as those addressed in economic theories have a significant effect on measurement choices. However, other reasons for adopting the plans, such as upgrading the workforce and linking bonuses to the firm's ability to pay, also influence measurement choices, as do union representation and management participation in plan design. Moreover, the factors influencing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(38 citation statements)
references
References 26 publications
1
35
0
Order By: Relevance
“…Therefore, our understanding of the antecedents and consequences of such systems in real‐world organizations is likely to be enhanced if researchers start out from a more comprehensive model of man than the “homo economicus.” The effect of performance reports on peers and the openness of information policies are only two important aspects that require attention. Other potentially fruitful avenues for future research include the number and types of performance measures (Ittner and Larcker [], Budde []), the relation between performance and pay in incentive contracts (Fehr and Fischbacher []), and the level of subjectivity in evaluation decisions (Ittner, Larcker, and Meyer [], Rajan and Reichelstein []).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our understanding of the antecedents and consequences of such systems in real‐world organizations is likely to be enhanced if researchers start out from a more comprehensive model of man than the “homo economicus.” The effect of performance reports on peers and the openness of information policies are only two important aspects that require attention. Other potentially fruitful avenues for future research include the number and types of performance measures (Ittner and Larcker [], Budde []), the relation between performance and pay in incentive contracts (Fehr and Fischbacher []), and the level of subjectivity in evaluation decisions (Ittner, Larcker, and Meyer [], Rajan and Reichelstein []).…”
Section: Discussionmentioning
confidence: 99%
“…Later agency works show analytically that the principal may take advantage of performance measures that the agent cannot fully control as long as they yield additional information about the agent's unobservable actions (Antle and Demski, 1988;Ittner and Larcker, 2002;Holmström, 1979;Milgrom and Roberts, 1992). Researchers have found this argument to be relevant in multi-agent settings as well (Baiman and Demski, 1980;Holmström, 1982).…”
Section: Review Of Prior Literature On the Controllability Principlementioning
confidence: 99%
“…Despite this rationale for the application of the principle, there are compelling arguments as to why organizations should not always fully conform to it. Companies can direct managers' attention to critical performance areas and gain additional information about their hidden actions by partially disregarding the principle (Ittner and Larcker, 2002;Manzoni, 2002;Simons, 2007). Given the convincing arguments both for and against applying the controllability principle, prior studies not surprisingly found that companies differ in the extent to which they follow the principle in formal performance evaluations (Drury and El-Shishini, 2005;Huffman and Cain, 2000;Vancil, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Prior literature suggests that compensation contracts are designed to meet multiple objectives and that the choice of performance metrics in a given reward system is affected by organizational objectives for that system (Ittner and Larcker, 2002). Profit sharing plans are generally designed to meet economic or information sharing objectives (Lawler, 1989, p. 163).…”
Section: Overview Of Profit Sharing Plansmentioning
confidence: 99%